RAILWAY CROSSING MONITORING BY CAMERA USING OPTICAL FLOW ESTIMATION (Perner's Contacts, 2010)
The content of this article is description of the issue of railway crossing monitoringusing methods of optical flow estimation. The methods were programmed eitherdirectly in Matlab or using Simulink Blocksets.
Keywords: Railway crossing monitoring; image processing; optical flow; Matlab; Simulink